2009
DOI: 10.1111/j.1439-0507.1971.tb02936.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Pityriasis Versicolor in Egypt

Abstract: Zusammenfassung 200 Patienten mit Pityriasis versicolor zeigten die typischen Krankheitserscheinungen am häufigsten an der Brust. In der Verteilungshäufigkeit folgten dann Hals und Schulterregion ohne große Unterschiede in beiden Geschlechtern. Als relativ beste Behandlung erwies sich die Anwendung von Tolnaftat sowie von schwefelhaltigen Zubereitungen wie Schwefelsalbe und Natriumthiosulfat. Tolnaftat wirkte besonders gut bei umschriebenen Herden. Es wird empfohlen, die Behandlung nach Eintreten der Repigment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Mbuagbaw et al46 found a female predominance, while no differences were found in other studies 19,27. A male preponderance was also reported for dermatophytosis,19,47,48 pityriasis versicolor,31,49,50 and nevi 33,41,51,52. However, two studies were found that reported a higher frequency of pityriasis versicolor in females 10,53…”
Section: Discussionmentioning
confidence: 90%
“…Mbuagbaw et al46 found a female predominance, while no differences were found in other studies 19,27. A male preponderance was also reported for dermatophytosis,19,47,48 pityriasis versicolor,31,49,50 and nevi 33,41,51,52. However, two studies were found that reported a higher frequency of pityriasis versicolor in females 10,53…”
Section: Discussionmentioning
confidence: 90%
“…Egyptian sugar cane molasses contain about 44% as total sugar (glucose, sucrose, and fructose), 0.46% as total nitrogen in addition to detectable amounts of some vitamins such as riboflavin and thiamin [46, 47]. Lai et al [48] reported that the main chemical characteristics of rice husk contain: carbon (45.3%), hydrogen (5.5%), nitrogen (0.67%), sulfur (0.29%), and chlorine (0.29) in addition to detectable amounts of potassium (1630 ppm), calcium (94 ppm), iron (202 ppm), sodium (207 ppm), zinc (24 ppm), magnesium (699), phosphorus (94 ppm), and other.…”
Section: Resultsmentioning
confidence: 99%
“…reported highest prevalence in the third and fourth decade of life. [ 22 ] In the study by Akapata et al . it was found that majority of cases occurred during adolescence.…”
Section: Discussionmentioning
confidence: 99%